2015
DOI: 10.14716/ijtech.v6i5.1041
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Freight Distribution Model for Connecting Inter-island Freight Transport

Abstract: Inter-island freight transport costs in eastern compared to western Indonesia are relatively high, caused by operator charges for roundtrip fees. In order to make the distribution of freight efficient, the network of freight transport needs to be rationalized on a regional basis. The output from the regional model counts are few and far between in relation to intercity traffic volume data, and the disaggregate model at a regional level requires more effort in conducting travel route surveys. Therefore, aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Many studies related to access to education, data sources, and the archipelago economy are severely constrained by geographical conditions (del Rosario & Kitada. 2020; Alejo, 2018;Sonny et al, 2015). Thus, the role of transportation infrastructure is significant to increase accessibility between regions to support all community activities.…”
Section: Literature Review 21 Supply Of the Energy To Accessibility And Pricementioning
confidence: 99%
“…Many studies related to access to education, data sources, and the archipelago economy are severely constrained by geographical conditions (del Rosario & Kitada. 2020; Alejo, 2018;Sonny et al, 2015). Thus, the role of transportation infrastructure is significant to increase accessibility between regions to support all community activities.…”
Section: Literature Review 21 Supply Of the Energy To Accessibility And Pricementioning
confidence: 99%
“…The chosen route must minimize distribution costs. The distribution network system in Indonesia is considered not efficient [1]. Although the distance is close, the distribution costs are not necessarily cheap, and vice versa.…”
Section: Sem Model Interpretationmentioning
confidence: 99%
“…As a continental region, population and economic conditions influence the amount of freight demand in the archipelago region. The types of vessels used to service these islands vary depending on the type and size of the freight to be transported [1]. In Indonesia, there are types of vessels that receive subsidies from the government (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to UFT, Bacarense et al used the MEM to estimate freight flows from secondary data in Belo Horizonte (Brazil) ( 39 ). Sonny et al valuated the origin–destination matrix of the regional goods flow from the northern Indonesian region of Maluku, integrating elements of urban planning and transport planning to analyze intracity cargo flows ( 40 ). Using Canadian GPS data, Gingerich et al identified stationary trucks ( 41 ), and You and Ritchie tracked truck routes in the San Pedro Bay ports (United States) ( 42 ).…”
mentioning
confidence: 99%